Better together: synergy in nanocellulose blends - Mautner,A; Mayer,F; Hervy,M; Lee,K-Y; Bismarck,A (Philosophical Transactions of the Royal Society A. Mathematical, Physical and Engineering Sciences, 2017)
Cellulose nanopapers have gained significantattention in recent years as large-scale reinforcementfor high-loading cellulose nanocomposites, substratesfor printed electronics and filter nanopapers forwater treatment. The mechanical properties ofnanopapers are of fundamental importance forall these applications. Cellulose nanopapers cansimply be prepared by filtering a suspension ofnanocellulose, followed by heat consolidation. It wasalready demonstrated that the mechanical propertiesof cellulose nanopapers can be tailored by the finenessof the fibrils used or by modifying nanocellulosefibrils for instance by polymer adsorption, butnanocellulose blends remain underexplored. In thiswork, we show that the mechanical and physicalproperties of cellulose nanopapers can be tuned bycreating nanopapers from blends of various gradesof nanocellulose, i.e. (mechanically refined) bacterialcellulose or cellulose nanofibrils extracted fromnever-dried bleached softwood pulp by chemical andmechanical pre-treatments. We found that nanopapersmade from blends of two or three nanocellulosegrades show synergistic effects resulting in improvedstiffness, strength, ductility, toughness and physicalproperties.This article is part of a discussion meeting issue‘New horizons for cellulose nanotechnology’.